2001
DOI: 10.1073/pnas.141225698
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of DNA gyrase inhibition by microcin B17 analogs with altered bisheterocyclic sites

Abstract: M icrocins are a class of small antibiotics (Ͻ10 kDa) produced and excreted by some strains of Enterobacteriaceae at the stationary phase of growth (1). Microcin B17 (MccB17) is a ribosomally synthesized compound that is produced in Escherichia coli harboring the plasmid-borne mcb operon, which contains the genes necessary for antibiotic synthesis, dedicated export, and immunity (2). The production of mature MccB17 ( Fig. 1) involves posttranslational modification of a 69-residue polypeptide-precursor to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
1
35
1
Order By: Relevance
“…We investigated the effect of MccB17 on ATP-independent relaxation by gyrase and found that the inhibition of this reaction by the toxin was also slow and incomplete. These results show that MccB17 inhibits supercoiling and relaxation of gyrase to a similar extent, and contrary to earlier reports (9,11), the action of MccB17 is not ATP-dependent. In contrast with MccB17, quinolones were shown to rapidly and completely inhibit the supercoiling and relaxation reactions of gyrase (36 -38).…”
Section: Effect Of Mccb17 On Supercoiling and Relaxation-previouscontrasting
confidence: 92%
See 4 more Smart Citations
“…We investigated the effect of MccB17 on ATP-independent relaxation by gyrase and found that the inhibition of this reaction by the toxin was also slow and incomplete. These results show that MccB17 inhibits supercoiling and relaxation of gyrase to a similar extent, and contrary to earlier reports (9,11), the action of MccB17 is not ATP-dependent. In contrast with MccB17, quinolones were shown to rapidly and completely inhibit the supercoiling and relaxation reactions of gyrase (36 -38).…”
Section: Effect Of Mccb17 On Supercoiling and Relaxation-previouscontrasting
confidence: 92%
“…It is expected that the effect of Ca 2ϩ is due to its substitution for Mg 2ϩ in the cleavage-religation process. Interaction of MccB17 with Gyrase-From our data and previous work (9,11), the action of MccB17 on gyrase is clearly distinct from that of quinolone drugs, such as ciprofloxacin, even if they both stabilize the cleavage complex. Quinolones completely inhibit the supercoiling and relaxation reactions of gyrase, and their effects can be rationalized from their proposed interaction with the distorted DNA (G segment) at the enzyme active site (44).…”
Section: Effect Of Mccb17 On Supercoiling and Relaxation-previoussupporting
confidence: 56%
See 3 more Smart Citations